Sports Service / Muhammad Farhan Mansor - Mansor, Muhammad Farhan (2020)
Entrepreneurship education aims to provide students with the knowledge, skills and motivation to build entrepreneurial success in a variety of environments. Variations in entrepreneurial education are offered at all levels of schools from primary or secondary through graduate university programs Entrepreneurship education focuses on the development of skills or attributes that enable realization of opportunities, where management is focused on the best way to manage the existing hierarchy. Both approaches have an interest in achieving "profit" in some form. In particular, the project was designed to meet the objectives of the assignment aimed at ensuring the students can see the growth and growth of the company's options based on their research and interviews. This project will help students identify the differences and similarities between the syllabus and the application conducted at the company that has been chose. The project must be able to find an efficient work environment that is compatible with the work space and scope of the employees in the business. The environment will reflect the quality and long-term value of the company in the future. This research will also demonstrate the efficiency of company rules and regulations or their standard operating procedures. Our company of choice is B-TOP PLT that provides a football academic program among youngster and teenagers. The main purpose of this company is to polish football skills among them. The company held many activities such as football or futsal tournaments to give a better experience to the participant. The CEO of this company obviously got a wealth of knowledge in sports and dedicated in building a strong sportsmanship among youngster and teenagers.